AN ANALYSIS OF PSYCHOPATHIC TRAITS TOWARDS ANNIE WILKES IN MISERY NOVEL BY STEPHEN KING - Sri Yadriha; Ana Mariana (Universitas Muhammadiyah Gorontalo, 2019)
Psychopath is abnormal psychology that cause pasients have difficulty in adjusting to the social norms that exsist in the environment. Basically psychopath is more known as a social predator because they likes to kill and rape their victims. This research focused on the psychopathic traits in one of the character in Misery novel named Annie Wilkes. This research used descriptive qualitative method and Robert D. Hare’s theory to reveal psychopathic traits shown by Annie Wilkes. The result of this research, there are eleven psychopathic traits in Annie Wilke. That are egocentric, lack of empathy, lack of concern for others, impulsivity, poor behavioral control, have an attractive outward appearrance, shallow emotions, have no fear, high posses feelings for personal satisfication, have a cruel social relationship with others and anti- social.